The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jhet.3582
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Aminonitriles and 5‐Substituted 1H‐Tetrazoles Using an Efficient Nanocatalyst of Fe3O4@SiO2–APTES‐supported Trifluoroacetic Acid

Abstract: Fe3O4@SiO2–APTES‐supported trifluoroacetic acid nanocatalyst was used for the one‐pot synthesis of α‐aminonitriles via a three‐component reaction of aldehydes (or ketones), amines, and sodium cyanide. This method produced a high yield of 75–96% using only a small amount of the catalyst (0.05 g) in EtOH at room temperature. The catalyst was also employed for the synthesis of 5‐substituted 1H‐tetrazoles from nitriles and sodium azide in EtOH at 80°C. The tetrazoles were produced with good‐to‐excellent yields in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Afterward, the product was collected by centrifugation and washed thoroughly with ethanol. Finally, the collected product, ZnO@SiO 2 @APTES, was dried in an oven at 60°C for 8 hr (Fatahi et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Afterward, the product was collected by centrifugation and washed thoroughly with ethanol. Finally, the collected product, ZnO@SiO 2 @APTES, was dried in an oven at 60°C for 8 hr (Fatahi et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Jafarzadeh et al 134 demonstrated that Fe 3 O 4 @SiO 2 @PrNH 2 -supported trifluoroacetic acid (CF 3 COOH, TFA), Fe 3 O 4 @SiO 2 @PrNH 2 . TFA works well as a nanocatalyst in the S-3-CR condensation of aldehydes (or ketones), amines, and sodium cyanide (but not TMSCN) in ethanol at room temperature to afford the respective tertiary or quaternary α-amino nitriles 27–28 (types I, III and IV).…”
Section: Fe 3 O 4 @Sio ...mentioning
confidence: 99%
“…Interestingly, Jafarzadeh et al 134 demonstrated that Fe 3 -O 4 @SiO 2 @PrNH 2 -supported triuoroacetic acid (CF 3 COOH, TFA), Fe 3 O 4 @SiO 2 @PrNH 2 .…”
Section: Mesoporous Molecular Sievesupported Metal Complexesmentioning
confidence: 99%
“…The synthesized nano-catalyst produced target tetrazoles in excellent yields in short reaction time of 4 h. Along with this, nano catalyst was easily recovered from external magnet and reused several times without significant loss of catalytic activity. 48 Similarly, structurally diverse wide library of 5-substituted-1 H -tetrazoles drug-like molecules was synthesized by Ashraf et al by introducing new magnetic nano-catalyst Fe 3 O 4 @ l -lysine-Pd(0) catalyzed protocol ( Table 2 , entry 9). The Fe 3 O 4 @ l -lysine-Pd(0) catalyzed green sustainable protocol involved [3+2] cycloaddition reactions of various aryl nitriles (1.0 mmol) possessing either electron-withdrawing or electron-donating substituents with sodium azide (1.3 mmol) in water.…”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%